Musculoskeletal Disorders In Countryside Fishermen Of Amazonas-Brazil - Ramos Fragoso, Jordana; Faccin Borges, Grasiely; Lima de Oliveira Carvalho, Marina; Sousa Ramos, Murilo (O Mundo da Saúde, 2018)
The postures adopted during fishing work can increase the rise of pain and discomfort, worsening the health risks of fishermen. To identify the prevalence of musculoskeletal disorders in fishermen working in the interior of the State of Amazonas, Brazil. A descriptive cross-sectional study was conducted in the fishery sector in the city Coari AM (SINPESCA). The Nordic Musculoskeletal Questionnaire (QNM) and the Couto Checklist were applied. Of the 40 fishermen, the most affected areas by musculoskeletal disorders identified in 30 men were the upper back (63.3%), lower back (50.0%), knees (46.7%) , shoulders (36.7%) and elbows (33.3%), and among the 10 women the most affected areas were upper back (80.0%), hand/ wrist (60.0%), lower back (50.0%), shoulder (50.0%) and knees (40.0%). All fishermen had biomechanical factors indicating risk and high risk. The indicated presence of musculoskeletal disorder risks can be seen especially in anatomical regions of the upper and lower back. There is the need apply preventive measures, as well as continuing education in the area of occupational health.